"I am willing to do both well": Chinese academic mothers facing tension in family and career. - Bao, Li; Wang, Guanghua (Frontiers in psychology, 2022)
Academic mothers perform intersected roles. They carry out their profession in workplaces, while they take the "second shift" of motherhood back to their families. The contested expectations in family and career built by the heterosexual matrix cause tension to academic mothers. We qualitatively investigate the interview data of six Chinese women academics on how they perform to negotiate their motherhood and academic work in the context of Chinese higher education, driven by the Butlerian theoretical concept of the heterosexual matrix. The findings suggest that Chinese academic mothers play a zero-sum game between being mothers and being academics, deriving from their ontological responsibilities of motherhood. We conclude that in the masculine academia, these women academics help maintain the heterosexual matrix by satisfying the gender normativity when they negotiate their performances in their family and career; meanwhile, most have developed some strategies to achieve their career advancement.; Competing Interests: The authors declare that the research was conducted in the absence of any commercial or financial relationships that could be construed as a potential conflict of interest. (Copyright © 2022 Bao and Wang.)
Keywords: 2000 à aujourd'hui; 2020-2029; approches et analyses; asie; chine; conciliation famille-travail; famille; femmes* universitaires; hétérosexisme; maternité; matrice hétérosexuelle; projet charge mentale; périodes historiques; ressource en ligne; régions géographiques; sexisme; systèmes d'oppressions; thématiques; travail

Territoires en mouvement : femmes et danses de résistance en Arménie - Institut de recherches et d'études féministes
Et si danser devenait un acte de résistance, un territoire à soi quand tout disparaît ? Dans cet épisode, nous partons en Arménie avec Sona Pogossian, où la danse devient un pilier identitaire face à l’enclavement, à la perte de terres, et aux blessures de l’histoire. La danse, architecture vivante et mouvante, est un territoire immatériel que l’on porte en soi. Les femmes y incarnent un double pilier : celui de la mère et celui de la nation. Dans une société où la femme est le noyau de l’identité nationale, comme dans bien d’autres luttes pour l’autodétermination, la figure maternelle devient le symbole d’un « NOUS » collectif, profond et résistant. Biographie : Artiste de la scène, Sona a suivi de multiples formations en anthropologie et pratiques des arts scéniques, dont au sein du conservatoire de Lyon, de l’université d’État de Moscou d’Art et de Culture, de l’université Paris 8, entre autres. Son parcours pluriel l’amène aujourd’hui à réaliser un doctorat (thèse-création) à l’UQAM en études et pratiques des arts, où elle tente de mettre en lumière les corporalités des femmes en phénomène de guerre. Enregistré durant la Tournée des cégeps à l’automne 2024 (https://iref.uqam.ca/babillard/tournee-des-cegeps-foire-feministe-feministes-dans-la-cite/)par Juliette Chevet et Rajae Anys. Écrit et monté par Rajae Anys. Avec le soutien financier du CRSH.
Keywords: 2000 à aujourd'hui; 2020-2029; Arménie; arts; asie; danse; discipline; doits des femmes; foire féministe; guerre; maternité; militance; musique; patriarcat; périodes historiques; régions géographiques; systèmes d'oppressions; thématiques